SOME SCHOLARLY ENGLISH PERIODICALS IN PRE-INDEPENDENT MALAYSIA: AN HISTORICAL OVERVIEW - Tiew, W.S. (Malaysian Journal of Library and Information Science, 1999)
Attempts to survey ten early Malaysian scholarly English periodicals which emerged during the pre-independent era. The study found that since 1847, certain individuals, learned associations, societies, government agencies or research institutions published scholarly periodicals in this region. Nevertheless, the growth in the number of these periodicals was rather slow, however, the momentum picked up after Independence on the 31st August 1957.